2015
DOI: 10.1152/ajprenal.00463.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between HIF-1α and AMPK in the regulation of cellular hypoxia adaptation in chronic kidney disease

Abstract: Renal hypoxia contributes to chronic kidney disease (CKD) progression, as validated in experimental and human CKD. In the early stages, increased oxygen consumption causes oxygen demand/supply mismatch, leading to hypoxia. Hence, early targeting of the determinants and regulators of oxygen consumption in CKD may alter the disease course before permanent damage ensues. Here, we focus on hypoxia inducible factor-1α (HIF-1α) and AMP-activated protein kinase (AMPK) and on the mechanisms by which they may facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Using models for renal disease, Li et al showed that HIF-1α and AMPK were linked at a molecular level during the response to hypoxic stress in the pathophysiology of CKD. AMPK activation was decreased in the subtotal nephrectomy model and was markedly restored by HIF-1α activation41. In our study, we speculate that HIF-1α did not function normally and AMPK may not have been fully restored by HIF-1α to facilitate cellular adaptation to hypoxia, resulting in cellular hypertrophy.…”
Section: Discussionmentioning
confidence: 61%
“…Using models for renal disease, Li et al showed that HIF-1α and AMPK were linked at a molecular level during the response to hypoxic stress in the pathophysiology of CKD. AMPK activation was decreased in the subtotal nephrectomy model and was markedly restored by HIF-1α activation41. In our study, we speculate that HIF-1α did not function normally and AMPK may not have been fully restored by HIF-1α to facilitate cellular adaptation to hypoxia, resulting in cellular hypertrophy.…”
Section: Discussionmentioning
confidence: 61%
“…Autophagy regulation in other CKD models or conditions is less clear. In the 5/6 th nephrectomy model of CKD, Li H et al showed evidence of autophagy suppression in kidneys, including decreases in LC3II and accumulation of P62 140 . However, in the same model Fedorova et al detected the up-regulation of autophagy genes (eg.…”
Section: Potential Mechanisms Underlying the Susceptibility Andmentioning
confidence: 99%
“…Another important molecular regulator of renal oxygenation is hypoxia inducible factor-1 alpha (HIF-1α). This transcription factor regulates several downstream proteins in oxygen delivery and consumption and plays an important role in the cellular response to hypoxia [7]. …”
Section: Renal Oxygenation and Hemodynamicsmentioning
confidence: 99%